Drug information a guide for pharmacists - Malone, Patrick M.; Kier, Karen L.; Stanovich, John E. (McGraw-Hill Medical, 2012)
"Everything pharmacists need to know about managing drug information for better patient outcomes Drug Information: A Guide for Pharmacists, 4e teaches pharmacists how to more effectively and efficiently research, interpret, collate and disseminate drug information in the most usable form possible. The book discusses how to determine what information is needed and how to respond adequately to requests for information. It also covers the ethical and legal aspects of drug information management. Features NEW coverage of patient safety, project design and organizational problem solving NEW key points added to each chapter NEW case studies added to add real world relevance NEW study questions integrated throughout the chapters "--Provided by publisher